Application of benson relaxation therapy and progressive muscle relaxation on sleep quality in hypertensive patients in Linggasari Village, Ciamis Regency - Zen, Dini Nurbaeti; Anggraeni, Dewi; Nurhayati, Nurhayati; Anwar, Syamsul; Wibowo, Daniel Akbar (Science Midwifery, 2024)
Most elderly people with hypertension have poor sleep quality. Poor sleep quality in elderly people with hypertension can worsen their hypertension condition, causing an increased risk of heart disease, cognitive impairment, and a general reduction in quality of life. Benson relaxation therapy and progressive muscle relaxation can be an effective and safe alternative in managing sleep and activity in elderly people with hypertension. Both therapies do not involve the use of drugs and can be easily learned by seniors. This study aims to determine the effect of Benson relaxation therapy and progressive muscle relaxation on sleep quality in hypertensive elderly people. This research uses a quasi-experimental method with a one group pretest posttest design. Data collection used the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The sample was determined using purposive sampling with a total of 35 respondents. The statistical results of the paired sample t-test showed a p value of 0.000 (p value < α 0.05) so it can be concluded that there is an influence of Benson relaxation therapy and progressive muscle relaxation on sleep quality in hypertensive elderly people. This study suggests integrating progressive muscle relaxation interventions combined with Benson therapy into community health programs by actively involving families.